Russian Attempts on Constitutional Issue of Insurgent Serbia (1804-1813) - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
As a result of the peace-treaty between France and Russia in Tilsit (July 7, 1807), a truce was concluded between Russia and Turkey in Slobozia (August 12, 1807). The peace treaty from Slobozia had a great importance for Serbian insurgents because it was the first act where Russia demonstrated its protection of Serbia. That way, at the end of 1807, the Serbian Uprising was crowned with successes on all fields. The country was liberated from the Turks, the mighty protection of Russia was ensured and the economic activities increased. It was under such circumstances that Karađorđe received on May 13, 1808, a leter from Russian field marshal Alexander Prozorovski (1732-1809), commander-in-chief of Russian Danubian army situated in Moldavia. The letter contained advices concernig the social and constitutional organization of Serbia. Karađorđe should use the truce for further securing of the peace in Serbia, through wise and useful decrees. Those ordinances, according to Prozorovski, would be the following: 1) to secure free settlements of Christians in Serbia; 2) to help and to protect the free market; 3) to ensure safety of life and property; 4) nobody can be punished without a sentence handed down by the court; 5) to fix the salary for the Vožd, members of the Senate and other chieftains. In his letter dated June 3, 1808, Karađorđe expressed gratitude to Prozorovski, expressing the wish to visit him in his headquarters. However, political and military circumstances prevented the desired meeting, but some of Prozorovski’s advice was already realised in Serbia. In September 30/October 12, 1808, the so-called Erfurt Convention was signed between Napoleon and Russian Emperor Alexander I. Although Serbia was not mentioned in the text of the Erfurt Convention, the fact that Napoleon and Alexander I recognize the integrity of the Ottoman Empire and that France renounces its mediation in future negotiations between Russia and Turkey, put Serbian insurgents in a very difficult situation. The recognition of the integrity of the Ottoman Empire, meant that Serbia would remain a part of the Ottoman Empire. The French renunciation of mediation meant that Russia would negotiate alone with Ottoman Empire and that the Serbian issue will be in connection with Russian political interests in the Balkans. However, while preparing the negotiations for the peace-treaty with Turkey, commander-in-chief of Russian Danubian army Prince Alexander Alexandrovich Prozorovski asked the proposals from Russian envoy in Serbia, Constantine Constantinovich Rodofinikin, concerning the provisions which would treat Serbia. Prozorovski especially asked Rodofinikin’s opinion regarding the borders of Serbia, its trade, Serbian relationships with other countries, the organization of supreme power, laws, the tribute payed to the Sublime Porte, and taxes. Due to the international political situation that changed to the detriment of Russia, all Russian attempts to find a solution to the basic constitutional issue for Serbia remained a dead in the water.